Resource reallocation under persistent immune activation drives trade-offs between life history and immunity in pirk-deficient Musca domestica - Ting Tang; Lan Yang; Liya Ma; Yu Ren; Mengnan Li; Shufan Guo; Xin Wang; Yuming Zhang; Fengsong Liu (BMC Biology)
Abstract Background The activation of the immune system by pathogens imposes significant energetic costs on hosts, which may result in the diversion of resources away from other non-essential biological processes, such as growth and reproduction. The underlying mechanisms of trade-offs between immune responses and host fitness remain poorly understood. Results We used a Musca domestica mutant (pirk-KO) to evaluate the influence of non-infection-induced immune system activation on female reproduction and larval growth. Pirk, a negative feedback inhibitor of the immune deficiency (Imd) pathway expressed in intestine and fat body, was induced by bacteria. pirk loss enhanced the immune response of house flies, reflected in sustained upregulated antimicrobial peptide gene expression and improved resistance to bacterial infections. The phenotypic traits of pirk-KO house flies, including delayed larval growth, reduced the body weight, and impaired female fertility, were indicative of the adaptive costs associated with aberrant immune activation. The transcriptional heterogeneities between pirk-KO and wild-type (WT) male flies indicated the overactivation of the Imd signaling pathway, accompanied by significant metabolic adaptations to the loss of pirk. The upregulation of pivotal genes involved in glycolysis and the TCA cycle indicated an enhanced central carbon metabolism in pirk-KO. The downregulation of multiple key enzymes involved in the pentose phosphate pathway in pirk-KO flies suggests a reduction in metabolic flux through the pentose phosphate pathway, which in turn results in impaired anabolism. The collective findings indicate that the pirk-KO flies undergo metabolic reprogramming to increase ATP production as a response to excessive immune activation, rather than incorporating nutrients into cellular biomass for cell proliferation. The pirk-KO flies exhibited a significantly elevated food intake and elevated levels of free glucose, trehalose, and fructose in comparison to the WT flies. Nevertheless, the glycogen and triglyceride contents in the pirk-KO flies were observed to be slightly diminished in comparison to the WT group. Conclusions When the immune defense is activated, the flies extract more free energy to fuel the immunological deployment by increasing nutrient intake, as well as reducing resource allocation to non-essential life-history traits, primarily reproduction and growth.